A new protocol for long‐term culture of a specific subpopulation of liver cancer stem cells enriched by cell surface markers - Zhang, Biao (FEBS Open Bio, 2020)
Liver cancer stem cells (L‐CSCs) are considered to be an important therapeutic target for hepatocellular carcinoma (HCC). This study provides a new in vitro long‐term culture model for a specific subpopulation of L‐CSCs enriched by cell surface markers. We combined CD13, CD133 and EpCAM to selectively enrich L‐CSCs, which we then cultured in modified chemically defined medium. The enriched L‐CSCs exhibited enhanced proliferation, self‐renewal and long‐term clonal maintenance ability as compared with non‐CSCs. Compared with wild‐type hepatocellular carcinoma, the expression of stemness surface markers, oncogenes, drug resistance and tumorigenicity in enriched L‐CSCs was significantly increased. In summary, the subpopulation of L‐CSCs still maintains cancer stem cell‐related phenotypes after 14 days of culture.